THE PSYCHOLOGICAL CHARACTERISTICS OF STUDYING TEENAGERS PRONE TO COMMITTING CRIMES (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article explores the psychological characteristics of teenagers who are prone to committing crimes. It examines various factors such as impulsivity, aggression, low self-control, and lack of empathy that contribute to delinquent behavior in adolescents. Understanding these psychological traits can aid in the development of preventive measures and interventions for at-risk youth.